1987
DOI: 10.1055/s-2007-1017103
|View full text |Cite
|
Sign up to set email alerts
|

Lithium: Clinical Study by Brain Electrical Activity Mapping. A Case Report

Abstract: One of the axes of research in our department is oriented on the study of the action of psychotropic drugs on the Central Nervous System by the means of the non invasive and direct techniques of cerebral imagery. First approach: EEG mapping In depressive states, the modification of nocturnal wakefulness states observed under lithium therapy begins to be well known. However, under lithium monotherapy, few diurnal studies have been performed. EEG mapping, based on a protocol and a strict methodology, could repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Studies performed on psychiatric patients mainly showed an increase of slow waves, slowing of the alpha rhythm, and the appearance of pathological patterns [Andreani et al, 1958;Kalinowsky and Hoch, 1961;Mayfield and Brown, 1966;Platman and Fieve, 1969;Johnson, 1969;Johnson et al, 1970;Helmchen and Kanowski, 1971;Itil and Akpinar, 1971;Bily et al, 1973;Gottschalk and Sack, 1973;Zakowska-Dabrowska and Rybakowski, 1973;Heninger, 1974;Okuma et al, 1974;Bente et al, 1982;Ulrich et al, 1982: Beaubernard et al, 1987, It should also be mentioned that the effect of lithium in epileptic patients remains controversial [Gershon, 1968;Erwin et al, 1973;Jus et al, 1973]. As for the serum lithium level measured in these dif ferent studies, it varied within as well as between studies considerably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed on psychiatric patients mainly showed an increase of slow waves, slowing of the alpha rhythm, and the appearance of pathological patterns [Andreani et al, 1958;Kalinowsky and Hoch, 1961;Mayfield and Brown, 1966;Platman and Fieve, 1969;Johnson, 1969;Johnson et al, 1970;Helmchen and Kanowski, 1971;Itil and Akpinar, 1971;Bily et al, 1973;Gottschalk and Sack, 1973;Zakowska-Dabrowska and Rybakowski, 1973;Heninger, 1974;Okuma et al, 1974;Bente et al, 1982;Ulrich et al, 1982: Beaubernard et al, 1987, It should also be mentioned that the effect of lithium in epileptic patients remains controversial [Gershon, 1968;Erwin et al, 1973;Jus et al, 1973]. As for the serum lithium level measured in these dif ferent studies, it varied within as well as between studies considerably.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one paper in which EEG mapping techniques were applied to de scribe the effect of lithium. Beaubernard et al [1987] reported a single case study with a patient with affective disorders under lithium monotherapy. They found an increase of theta and alpha power under resting condi tions with eyes closed.…”
Section: Introductionmentioning
confidence: 99%